2016
DOI: 10.1152/ajpcell.00362.2015
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 regulates platelet integrin activation, granule secretion and aggregation

Abstract: Rigg RA, Healy LD, Nowak MS, Mallet J, Thierheimer ML, Pang J, McCarty OJ, Aslan JE. Heat shock protein 70 regulates platelet integrin activation, granule secretion and aggregation. Molecular chaperones that support protein quality control, including heat shock protein 70 (Hsp70), participate in diverse aspects of cellular and physiological function. Recent studies have reported roles for specific chaperone activities in blood platelets in maintaining hemostasis; however, the functions of Hsp70 in platelet phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
(60 reference statements)
2
35
0
Order By: Relevance
“…E). To test whether the ATPase activity of GRP78 was indeed unnecessary for protection, this experiment was repeated in isomerization buffer in the absence of ATP and in the presence of an inhibitor of GRP78, namely VER‐155008 . In the presence of its inhibitor, GRP78 also suppressed the isomerase activity of PDIA6 against opMPD indicating that ATPase activity was not needed for this process (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E). To test whether the ATPase activity of GRP78 was indeed unnecessary for protection, this experiment was repeated in isomerization buffer in the absence of ATP and in the presence of an inhibitor of GRP78, namely VER‐155008 . In the presence of its inhibitor, GRP78 also suppressed the isomerase activity of PDIA6 against opMPD indicating that ATPase activity was not needed for this process (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the influence of endogenous GRP78 on the shedding activity of ADAM17, cells were treated with an inhibitor of GRP78 (VER‐155008 ) at 15 min prior to and during stimulation of ADAM17 (Fig. B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SurvExpress database showed that patients with high mortalin expression exhibited worse overall survival (OS) rates. Finally, CRC cell proliferation and EMT progression were inhibited by treatment with MKT‐077 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, CRC cell proliferation and EMT progression were inhibited by treatment with MKT-077. [15][16][17] 2 | MATERIALS AND METHODS…”
Section: Introductionmentioning
confidence: 99%
“…Heat‐shock protein 70 (HSP70), as a highly conserved protein, exists in all living cells and is produced following stimulation by hypoxia, ischaemia, viral infection and oxidants (Rigg et al, ). Furthermore, HSP70 is also an apoptosis‐associated protein that participates in the inhibition of the mitochondrial apoptotic and membrane receptor apoptotic pathways (Mao et al, ).…”
Section: Introductionmentioning
confidence: 99%